2021
DOI: 10.3390/en14185679
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Influence of Secondary Air Uniformity on Jet Penetration and Gas-Solid Diffusion Characteristics in a Large-Scale CFB Boiler

Abstract: The uniformity of secondary air (SA) in large-scale CFB boilers has an important influence on gas-solid flow and combustion, but was seldom considered in previous studies. Numerical simulation based on the Eulerian–Eulerian and RNG k-ε turbulence models was conducted to explore the influence of SA uniformity and load variation on jet penetration, diffusion characteristics and gas-solid mixing in the first 600 MW supercritical CFB boiler. The results showed that better SA uniformity was conductive to the unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…33,34 It is reported that the solid dispersion in a large-scale CFB boiler is vastly different from that in a laboratory-scale bed. 13,19,21 In addition, as particle size d p and density ρ p affect fuel dispersion characteristics, the particle property changing pattern might be an important effect. From previous studies, there are generally three treatments to describe the size and density change during combustion: particle size shrinkage with constant density, density decrease with constant size, and both particle size and density decrease simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 It is reported that the solid dispersion in a large-scale CFB boiler is vastly different from that in a laboratory-scale bed. 13,19,21 In addition, as particle size d p and density ρ p affect fuel dispersion characteristics, the particle property changing pattern might be an important effect. From previous studies, there are generally three treatments to describe the size and density change during combustion: particle size shrinkage with constant density, density decrease with constant size, and both particle size and density decrease simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Differing from the CFD-DEM model, the two-fluid model (TFM) is also applied. , Hernández-Jiménez et al used the TFM to study solid dispersion by setting two types of solid phases and evaluating the mixing completion level according to the relative volume fraction of two solid fluids. They found that it took little time to reach complete mixing with smaller particle sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation